Ergonomic design parameters for Malaysian car driver saeting postion - Zuli'zam Rashid, 1969-, author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Doktor Falsafah (Kejuruteraan Mekanikal)) - Universiti Teknologi Malaysia, 2017